The impact of international migration and remittances on the labor-supply behavior of those left behind: evidence from Egypt - Christine Binzel; Ragui Assaad (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We analyze in this paper the impact of male-dominated migration and remittance income on the participation and hours worked decisions of adults left behind, including the hours spent by women in subsistence and domestic work. We differentiate between a 'pure' migration (M) effect and the joint effect of migration and remittance income (MR) and evaluate these effects for men and women separately. Additionally, we examine the labor supply behavior of wives whose husband migrated. We draw on the 2006 cross section using an instrumental variable approach as well as on the 1998/2006 panel of the Egypt Labor Market Panel Survey (ELMPS06). In line with the literature, women in MR households (albeit not in M households) tend to reduce their wage and salary work. We find evidence for both intra-household specialization and an increase in women's (and wives') total work load. Men are generally less affected. Our results suggest that it is important to differentiate between these two effects and between the different forms of market and non-market work as well as to consider the relationship between remitter and recipient.
Keywords: O15; J22; F22; R23; 330; Migration; remittances; labor supply; time allocation; gender; Internationale Wanderung; Auswanderung; Männer; Rücküberweisung (Migranten); Frauenerwerbstätigkeit; Arbeitsangebot; Zeitallokation; Geschlecht; Ägypten